The Expression of Free Opinion through Graffiti and Murals in Kosovo and Serbia - Muharremi, Ilir; Krasniqi, Albana; Balidemaj, Atlanta (Street Art & Urban Creativity, 2023)
This work addresses the art of graffiti and murals in Kosovo and Serbia. Is graffiti political or not political? Are the murals in Kosovo and Serbia addressing similar political subjects? How much influence do the works of art possess? Murals and graffiti express culture in both Kosovo and Serbia. In Serbia, depictions of war leaders are on the walls of buildings all over the country. In Kosovo, how are the topics of the last war presented? Do real social themes influence the depictions of the murals? The graffiti and mural works in Kosovo are different from those in Serbia. Serbs still depict war themes in both graffiti and murals but in Kosovo, the topics are freer, still maintaining their subjectiveness to current political, social, economic, and legal topics. Free speech is as free as it is in murals and graffiti in two neighboring states that are American to each other.